The Effect of Three Different Disinfection Materials on Alginate Impression by Spray Method. (25th July 2012) - Badrian, Hamid; Ghasemi, Ehsan; Khalighinejad, Navid; Hosseini, Nafiseh
Abstract : Introduction . The aim of this study was to investigate the effect of three different types of disinfectant agents on alginate impression material after 5 and 10 minutes. Method and Materials . In this in vitro experimental study, 66 circular samples of alginate impression material were contaminated with Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans fungus. Except for control samples, all of them were disinfected with sodium hypochlorite 0.525, Deconex, and Epimax by way of spraying. Afterwards, they were kept in plastic bags with humid rolled cotton for 5 and 10 minutes. The number of colonies was counted after 24 and 48 hours for bacteria and after 72 hours for fungus. Statistical Mann-Whitney test was used for data analysis ( α = 0.05). Results . After 5 minutes, Epimax showed the highest disinfection action on Staphylococcus aureus as it completely eradicated the bacteria. The disinfection capacity of different agents can be increased as time elapses except for Pseudomonas aeruginosa which was eradicated completely in both 5 and 10 minutes. Conclusion . This study revealed that alginate can be effectively disinfected by three types of disinfecting agents by spraying method, although Epimax showed the highest disinfection action after 10 minutes compared to other agents.